Case Report: Sequential postzygotic HRAS mutation and gains of the paternal chromosome 11 carrying the mutated allele in a patient with epidermal nevus and rhabdomyosarcoma: evidence of a multiple-hit mechanism involving HRAS in oncogenic transformation - Zuntini, Roberta; Cattani, Chiara; Pedace, Lucia; Miele, Evelina; Caraffi, Stefano Giuseppe; Gardini, Stefano; Ficarelli, Elena; Pizzi, Simone; Radio, Francesca Clementina; Barone, Angelica; Piana, Simonetta; Bertolini, Patrizia; et al. (Frontiers in Genetics, 2023)
We report a 7-year-old boy born with epidermal nevi (EN) arranged according to Blaschko's lines involving the face and head, right upper limb, chest, and left lower limb, who developed a left paratesticular embryonal rhabdomyosarcoma at 18 months of age. Parallel sequencing identified a gain-of-function variant (c.37G>C, p.Gly13Arg) of HRAS in both epidermal nevus and tumor but not in leukocytes or buccal mucosal epithelial cells, indicating its postzygotic origin. The variant accounted for 33% and 92% of the total reads in the nevus and tumor DNA specimens, respectively, supporting additional somatic hits in the latter. DNA methylation (DNAm) profiling of the tumor documented a signature consistent with embryonal rhabdomyosarcoma (ERMS), and CNV array analysis inferred from the DNAm arrays and subsequent MLPA analysis demonstrated copy number gains of the entire paternal chromosome 11 carrying the mutated HRAS allele, likely as the result of paternal unidisomy followed by subsequent gain(s) of the paternal chromosome in the tumor. Other structural rearrangements were observed in the tumours, while no additional pathogenic variants affecting genes with role in the RAS-MAPK and PI3K-AKT-MTOR pathways were identified. Our findings provide further evidence of the contribution of "gene dosage" to the multistep process driving cell transformation associated with hyperactive HRAS function.